An Evaluation of Rock Slope Stability using Limit Equilibrium Analyses - Aprilia, Faridha (2014)
The stability of rock slopes is controlled by several factors, such as the intack rock strength, discontinuity characteristics, groundwater condition, and slope geometry. Limit equilibrium (LE) analyses have been commonly used in geotechnical practice to evaluate the stability of rock slopes. A number of methods of LE analyses, ranging from simple to sophisticated methods, have been developed. This paper presents stability analyses of rock slopes at the Batu Hijau open mine in Sumbawa Barat using various methods of LE analyses.